New Knowledge and Research Needs for End-of-Life Care Among Elderly Persons in Long-Term Care Settings - Sabrina Lessard; Bernard-Simon Leclerc (Journal of Aging Research And Healthcare, 2017)
Given the aging of the population, an increase in the number of persons in need of long-term care and end-of-life care can be expected in the coming years. The scientific literature underlines the lack of end-of-life care for elderly people in long-term care centres. The aim of this study is to explore needs in terms of new knowledge and research on end-of-life care for elderly persons in long-term care settings, from the perspective not only of the scientific and international community, but also of Quebec professionals concerned by the issue. An online survey using the LimeSurvey® tool was conducted in 2015 among health professionals involved in end-of-life care for elderly persons in long-term care settings in Quebec. 208 professionals rated the priority of new knowledge and research needs related to 1) health professionals; 2) delivery and quality of care; 3) residents and their loved ones; and 4) organization and management of care. The results show that the statements collected in scientific literature resonate with health professionals. The most important need is to identify the symptoms of distress in residents in the final stages of their lives, as well as their causes and treatments. This study also shows professionals’ concerns about attitudes, beliefs, and values of practitioners and the related impacts on end-of-life care in long-term care settings. This study shows that there is a significant need for new knowledge and research. It revealed that there are few studies on end-of-life care for elderly persons in long-term care settings and that there is much more to be discovered in this field.
Keywords: End-of-life care